PWE-011 Charting the Volatile Organic Metabolome (VOM): A Comparison of Murine and Human Faeces. (4th June 2013) - Sawbridge, D; Reade, S; Khalid, T; Probert, C
Abstract : Introduction: The metabolome is important in the development of IBD and colorectal cancer. It may be studied using gas chromatography mass spectrometry (GCMS) or electronic noses that sniff the volatile organic compounds, which comprise a large portion of the metabolome. However the healthy volatile organic metabolites (VOMs) of mice remain uncharted, nor have mouse models been validated for use in comparative studies of VOMs with humans. Methods: We collected serial samples from healthy C57 BL/6 mice and a healthy human, as part of our method development for VOM studies in colitis and colorectal cancer. The samples were enclosed in glass vials and the VOMs extracted from the headspace gas. VOMs were analysed using GCMS and the resultant fragmentation patterns compared to the NIST database for compound identification. VOMs from murine and human samples were compared. The consistency of mouse and human samples over time and between individuals was also examined by listing the rank position in quintiles over serial samples. Results: 60 individual VOMs were identified from mice and 87 in the human, with a 22% correlation between the two. Most notable in the murine sample was the high concentration of simple organic molecules such as hexane and short chain aldehydes. Several compounds were found in the murine sample that had not been seen in human samples and probably reflect urine contamination from incontinent mice. The greatest concentration of VOMs in the mouse were: hexanal, 2.2.4.6.6-pentamethyl-heptane and pentanal. By comparison, in the human, complex cycloalkenes and benzene-based compounds, such as 1-methyl-4-(1-methylethylidene)-cyclohexene, were in abundance. Chief compounds in the human were: D Limonene, 2-methyl phenol and indole. Several molecules were prominent in both mouse and human, such as acetone, short chain organic acids including hexanoic, pentanoic and butanoic acids and D-limonene. The more simple compounds likely reflect a combination of the metabolic effluvia of common intestinal microbiota and mammalian physiology. The position of VOMs in each quartile was found to be consistent with 86% recurrence in the first quartile, 71% in the last quartile. Conclusion: This is the first description of the VOC metabolome of C57 BL/6 mice. A comparison with human samples shows there is a low but notable correlation between the two species. Many of the VOCs present are by-products of microbial and cellular metabolism. The difference in number and complexity of the VOCs found in the human, compared with the mouse, may reflect varied diet and a more complex intestinal microbiome. Such data will allow calibration of future studies of colonic disease in humans and through the induction of colonic disease in mice. Disclosure of Interest: None Declared.